Development and Validation of a Physics Test Instrument to Measure Problem-Solving Skills on Heat Concepts - Adhelia Tasya Youlanda; Mukhayyarotin Niswati Rodliyatul Jauhariyah (Berkala Ilmiah Pendidikan Fisika, 2026)
This study aims to develop a valid and reliable knowledge test instrument to measure students’ problem-solving skills in heat material. The research employed a research and development approach using the ADDIE development model. The instrument consisted of 10 essay questions constructed based on Polya’s problem-solving indicators. The instrument was validated by three experts, specifically two lecturers in the physics department and one physics teacher, and also tested on thirty-three first-year students enrolled in the Physics Education Study Program at Surabaya State University. The analysis included theoretical validity, empirical validity, reliability, difficulty level, and discrimination power. The results showed that the theoretical validity reached an average Percentage of Agreement (PoA) of 88.09% in the valid category. Empirical validity indicated that all items (100%) were valid with a reliability coefficient of 0.83, indicating high reliability. The difficulty level consisted of 60% easy and 40% moderate items, while the discrimination power showed 10% good and 90% sufficient categories. These findings indicate that the developed instrument is suitable for measuring students’ problem-solving skills in heat material and supporting the assessment of higher-order thinking skills in physics learning.